David Cohen Just for you. Enjoy. [ATTACH=full]1912[/ATTACH]

prove that sin(A-B)/sin(A+B)=(a^2+b^2)/c^2 use identities: sin(A-B)=sin(A) cos(B) - cos(A) sin(B) sin(A+B)=sin(A) cos(B) + cos(A) sin(B) sin(A-B)/sin(A+B)=(sin(A) cos(B) - cos(A) sin(B))/(sin(A) cos(B) + cos(A) sin(B)) sin(A-B)/sin(A+B)=(2ac*cos(B)-2bc*cos(A))/(2ac*cos(B)+2bc*cos(A)) sin(A-B)/sin(A+B)=(a^2-b^2+c^2-(-a^2+b^2+c^2))/((a^2-b^2+c^2)+(-a^2+b^2+c^2)) sin(A-B)/sin(A+B)=(a^2-b^2+c^2+a^2-b^2-c^2)/(a^2-b^2+c^2-a^2+b^2+c^2) sin(A-B)/sin(A+B)=(2a^2-2b^2)/(2c^2) sin(A-B)/sin(A+B)=(a^2-b^2)/c^2